Tropical Cellulolytic Bacteria: Potential Utilization of Sugarcane Bagasse as Low-Cost Carbon Source in Aquaculture - Ren, Wei; Xu, Xueni; Long, Hao; Zhang, Xiang; Cai, Xiaoni; Huang, Aiyou; Xie, Zhenyu (Frontiers in Microbiology, 2021)
Sugarcane bagasse (SB), as a major by-product of sugarcane, is one of the most abundant organic matter and characterized by cheap and easily available carbon source in Hainan Island, China. The objective of this study was to isolate tropical cellulolytic bacteria from Hainan Island and demonstrate their prospects of utilization of SB as a low-cost carbon source to greatly reduce the cost of aquaculture. A total of 97 cellulolytic marine bacteria were isolated, of which, 58 cellulolytic marine bacteria displayed the hydrolysis capacity (HC) of more than 1, while 28 cellulolytic marine bacteria displayed more than 2. Of the 28 tropical cellulolytic bacterial strains with HC more than 2, Microbulbifer sp. CFW-C18 and Vibrio sp. MW-M19 exhibited excellent SB decomposition in a small-scale laboratory simulation of shrimp aquaculture, up to 75.31 and 74.35%, respectively, and both of them were safe for shrimps. Meanwhile, both of CFW-C18 and MW-M19 besides displaying low multiple antibiotic resistance (MAR) index, also increased the C/N ratio (CFW-C18: C/N ratio of 14.34; MW-M19: C/N ratio of 14.75) of the small-scale laboratory simulation of shrimp aquaculture by decreasing the nitrogen content after a supplement of SB for 15 days. More importantly, CFW-C18 and MW-M19 displayed a relatively low MAR index, 0.47 and 0.1, respectively, especially MW-M19, with the lowest MAR index (0.1), which was resistant to only three antibiotics, streptomycin, amikacin, and levofloxacin, indicating that this strain was safe and non-drug resistance for further use. Overall, tropical cellulolytic bacteria isolated from Hainan Island, especially CFW-C18 and MW-M19, will provide the proficient candidates as probiotics for further construction of the recirculating aquaculture system based on the supplement of low-cost external carbon source—SB.